Plaatsvervulling(Ahli Waris Pengganti) Disebabkan Murtad, Membunuh Serta Hilang (Mafqud) Menurut UU dan KHI & Analisis Dasar Putusan Pengadilan atau MA - Ritonga, Ali Bata; Tanjung, Dhiauddin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The position of the heir who has apostatized is a barrier for him to get the inheritance from the heir, this is because the distribution of inheritance must be given to heirs who are Muslim. The barrier to inheritance is killing. The majority of scholars agree that the heir who kills his muwarris is prevented from receiving an inheritance because his rights as an heir have fallen due to the murder. The killing of his prospective muwarris was an act that severed the ties of silaturrahmi between them as relatives. Kinship relationship is one of the causes of inheritance relations between muwarris and their heirs.